Influence of Dynamic Strength Index on Countermovement Jump Force-, Power-, Velocity-, and Displacement-Time Curves - John J. McMahon; Paul A. Jones; Thomas Dos'Santos; Paul Comfort (MDPI AG, 2017)
The dynamic strength index (DSI), often calculated as the ratio of countermovement jump (CMJ) propulsion peak force to isometric mid-thigh pull (IMTP) peak force, is said to inform whether ballistic or maximal strength training is warranted for a given athlete. CMJ propulsion peak force is highly influenced by jump strategy, however, which is not highlighted by the DSI alone. This study aimed to quantitatively compare CMJ force-, power-, velocity-, and displacement-time curves between athletes who achieved high versus low DSI scores. Fifty-three male collegiate athletes performed three CMJs and IMTPs on a force platform. Athletes were ranked based on DSI score and the CMJ kinetic and kinematic-time curves of the bottom and top twenty athletes were compared. The low DSI group (0.55 ± 0.10 vs. 0.92 ± 0.11) produced greater IMTP peak force (46.7 ± 15.0 vs. 31.1 ± 6.6 N·kg−1) but a larger braking net impulse in the CMJ, leading to greater braking velocity and larger countermovement displacement. This strategy resulted in a similar CMJ propulsion peak force (25.9 ± 2.2 vs. 25.4 ± 3.1 N·kg−1) to the high DSI group. These results, taken together with those of previous studies, support the notion of ballistic versus maximal strength training likely being better suited to low versus high DSI scorers, respectively.